Load curtailment minimization by optimal placement of Unified Power Flow Controller. (22nd March 2016) - Singh, Jai Govind; Qazi, Hassan Wajahat; Ghandhari, Mehrdad
Summary: In this paper, a new sensitivity‐based approach is proposed to minimize the load curtailment by optimal placement of series controller of the Unified Power Flow Controller (UPFC) in the power system. The proposed sensitivity factors are derived in terms of change in load curtailment with respect to change in UPFC series control parameters. The effectiveness of the proposed method has been investigated by formulating an optimal power flow problem with an objective to minimize the load curtailment. Results have been obtained on IEEE 14‐bus and IEEE 30‐bus systems. It has been shown that required load curtailment drastically reduced with placement of UPFC and could be effective in various operating conditions of power system. With this technique, a large amount of power curtailment could be avoided, hence, saved from revenue loss, social disobedience, and customer service interruption. Copyright © 2016 John Wiley & Sons, Ltd.